Skeletal changes, dental and face of class III skeletal malocclusion treated with philosophy MEAW (Multiloop Edgewise Arch Wire): a descriptive retrospective - Ángela Anyur García Bernal; Diana Lucía Cadena Pantoja; Daniel Mauricio Celis Ramírez; Jesús Arcesio Peñarredonda Lemus; Sylvia María Moreno Ríos; María Alejandra González-Bernal (Acta Odontológica Colombiana, 2013)
Background: One of the most complex problems about the diagnosis and treatment of malocclusions constitutes correcting skeletal Class III. Objective: to determine the skeletal changes, dental and facial skeletal Class III malocclusion treated with Edgewise philosophy Multiloop (MEAW) in patients who attended a private dental clinic from March 2009 to September 2012. Methods: We performed a retrospective study, which analyzed the clinical records of seven patients diagnosed with skeletal Class III malocclusion. Variables were assessed age, gender, initial and final cephalometric measurements on lateral radiographs and photographs. Results: 60% were women, convexity angle step from 10,58° a 16,4°; Dysplasia Indicator Antero- Posterior (APDI) decreased from 96,7° a 91,0°, while the Palatine Plano (PP) increase of 114,3°a 115,4° and the occlusal plane inclination increased from 17,8°a 24,7°. The average treatment time was 19,4 months. Conclusions: MEAW philosophy is a therapeutic alternative camouflage in the treatment of skeletal Class III malocclusions.